PENGARUH DEWAN KOMISARIS INDEPENDEN, PERTUMBUHAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Siti Putri rahayu; Septi Wulandari Chairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of independent commissioners, firm growth, and profitability on firm value in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The study employs a quantitative approach using panel data regression. The sample comprises nine mining companies selected through purposive sampling, resulting in 45 observations. The findings indicate that independent commissioners have a significant positive effect on firm value. However, firm growth and profitability do not show significant effects. These results support agency theory and signaling theory in the context of firm value. This study provides practical implications for stakeholders to enhance corporate value by strengthening governance mechanisms.